The scope of eurocrimes and their possible extension - Udvarhelyi, Bence (European Integration Studies, 2025)
Article 83(1) of the Treaty on the Functioning of the European Union empowers the European legislator to establish minimum rules concerning the definition of criminal offences and sanctions in the areas of particularly serious crime with a cross-border dimension. This legal harmonisation competence was frequently used by the EU and resulted in the adoption of several criminal law directives. The Treaty determines ten areas of crime which can subject to legal harmonisation and most of which have already been regulated at the EU level. The objective of the article is to provide a detailed analysis of the requirements of the legal harmonisation competence, the scope of harmonisation, its procedural conditions and the possibility of the extension of the list of EU crimes. The paper also intends to present and analyse the legislative practice of the EU institutions and tries to formulate the relevant tendencies in connection with the current EU criminal policy.